PROFIL PENASEHAT AKADEMIS (PA) DALAM PELAYANAN KONSELING KARIER DI PERGURUAN TINGGI - Zulva Zulfa (Universitas PGRI SUMATERA BARAT, 2018)
Higher education is one of the places that can be used as a forum in the intellectualization of the nation, one of the important components in higher education in educating dance children is academic advisor. But in fact many Academic Advisers (PA) in many universities do not function, one of them as a counselor in the academic field. At STKIP PGRI West Sumatra academic advisors involved lecturers as counseling services. This is very important because students need academic advisors as counselors who can understand the problems they face in the study period. The results of this study indicate that on campus STKIP PGRI West Sumatra PA has a very important role in advancing students in the academic field, as well as helping students in developing careers that they must choose or determine